Peningkatan Prestasi Belajar Melalui Model Pembelajaran Think Pairs Share (TPS) Pada Mata Pelajaran IPA Kelas IV SDN Tirtosari, Magelang - Wahyu Kurniawati; Dinda Ayu Rachmawati; Budiharti Budiharti; Deri Anggraini (Universitas Muhammadiyah Magelang, 2022)
The purpose of this study was to improve science learning achievement using the Think Pairs Share (TPS) learning model for class IV at SD N Tirtosari. This study uses PTK method. Data collection techniques with interviews, observations, field notes, and tests. Sources of data are teachers and students as research subjects. The data analysis technique is descriptively taken from the average achievement score and the percentage of student completeness. Based on the research, it was concluded that the use of the TPS learning model could improve the learning achievement of fourth grade students at SD N Tirtosari. In the pre-action the average student achievement was 69.28 with a completeness percentage of 42.85%, in cycle I it increased from 5.86 to 75.14 with a completeness percentage of 57.14% because it was not in accordance with the percentage of success then proceed to cycle II . In cycle II there was an average increase of 11.71 so that the average student achievement was 86.85 with a completeness percentage of 100%. From this description it can be seen that there has been an increase from the pre-action stage, cycle I to cycle II.